Trade‐Offs Between 1‐D and 2‐D Regional River Hydrodynamic Models. Issue 8 (19th August 2020) - Fleischmann, A. S.; Paiva, R. C. D.; Collischonn, W.; Siqueira, V. A.; Paris, A.; Moreira, D. M.; Papa, F.; Bitar, A. A.; Parrens, M.; Aires, F.; Garambois, P. A.
Abstract: Recent years have seen the development of 1‐D and 2‐D regional‐scale hydrological‐hydrodynamic models, which differ greatly from reach‐scale applications in terms of subgrid assumptions, parameterization, and applied resolution. Although 1‐D and 2‐D comparisons have already been performed at reach and local scales, model differences at regional scale are poorly understood. Moreover, there is a need to improve the coupling between hydrological and hydrodynamic models. It is addressed here by applying the MGB model at 1‐D and 2‐D dimensions for the whole 700, 000 km 2 Negro basin (Amazon), which presents different wetland types. Long‐term continuous simulations are performed and validated with multisatellite observations of hydraulic variables. Results showed that both approaches are similarly able to estimate discharges and water levels along main rivers, especially considering parameter uncertainties, but differ in terms of flood extent and volume and water levels in complex wetlands. In these latter, the diffuse flow and drainage patterns were more realistically represented by the 2‐D scheme, as well as wetland connectivity across the basin. The 2‐D model led to higher drainage basinwide, while the 1‐D model was more sensitive to hydrodynamic parameters for discharge and flood extent and had a similar sensitivity for water levels. Finally, tests on the coupling between hydrologic and hydrodynamic processes suggested that their representation in an online way is less important for tropical wetlands than model dimensionality, which largely impacts water transfer and repartition. Plain Language Summary: Hydrologic‐hydrodynamic numerical models are powerful tools for improving water resources and disaster management and for the understanding of hydrological processes. Last years have faced the development of regional‐scale applications (i.e., areas between 10 4 to 10 6 km 2 ), with approaches at both 1‐D and 2‐D dimensions, that is, by representing surface water transport in either one (along rivers) or two horizontal directions (in order to represent flood propagation in wetlands). In this study, we present a regional‐scale application of the MGB model at both 1‐D and 2‐D dimensions for the Negro River Basin in the Amazon and compare its capability to simulate processes at the basin scale and for different wetland types. We show that current 1‐D and 2‐D models are similarly capable to represent discharges and water levels along main rivers, but for more complex wetlands, the 2‐D models are required, especially for estimating water levels. We also show that for tropical wetlands, the consideration of feedbacks between hydrologic and hydrodynamics is less important than the dimensionality of the model (i.e., if it is 1‐D or 2‐D). New lessons on the functioning of complex river‐wetland systems in the Amazon are presented, in special consideration of the current availability of remote sensing data sets. Key Points: We develop a 2‐D regional‐scale coupled hydrologic‐hydrodynamic model in the light of multisatellite visibility 2‐D model better represents complex wetlands but provides similar results to 1‐D on discharge and water levels for large river networks Dimensionality is more important than coupling hydrological‐hydrodynamic processes to represent the hydraulics of complex tropical wetlands